Kebijakan Kriminal Terhadap Korban Investasi Binomo Binary Option dan Quotex Robot Trading di Indonesia: Criminal Policies Towards Victims of Binomo Binary Option and Quotex Robot Trading Investments in Indonesia - Artha Febriansyah; Frizky Hervando; Vera Novianti (Asosiasi Pengajar Hukum Pidana dan Kriminologi Indonesia (ASPERHUPIKI), 2024)
Illegal investments in Binomo binary option and Quotex robots have resulted in users experiencing large economic losses and psychological or mental losess. The research aims to explain criminal policies towards victims of illegal investments in Binomo binary option and Quotex robot trading in Indonesia along with the factors that influence the implementation of these policies. The research method used is normative legal research using statutory, conceptual and case approaches. From the research carried out, the results obtained are that the criminal policy against victims of illegal investment is carried out using non-penal policies through the OJK, Bappebti, Kemenkominfo and PPATK based on their functions, duties and authority, while the penal policy goes through the formulation or reformulation stage of the law if necessary, the application stage by applying criminal law to the perpetrator of the crime and the execution stage by implementing the court decision against the perpetrator with imprisonment, fines and confiscation of the proceeds of the crime. That, currently Indonesia legally has Ditreskrimsus and Ditipidsiber within the National Police and Jampidus elements within the Presecutor’s Office. In substance, Indonesia does not yet need new laws to regulate illegal investments and in terms of legal culture, users still have minimal financial services literacy, are technologically illiterate and are oriented towards big profits without looking at the legality of Binomo and Quotexx and not thinking about the negative impact.